2017
DOI: 10.1080/14787210.2017.1309974
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, long-term clinical outcomes, and prognostic factors of tuberculous meningitis in West China: a multivariate analysis of 154 adults

Abstract: Mortality and disability associated with TBM are high in China. Limb weakness, GCS scores, cranial-nerve palsy and hydrocephalus were independent predictors of poor outcomes, and AGR, NLR, D-dimer, and EEG abnormalities may be prognostic factors of TBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
2
24
2
Order By: Relevance
“…The study populations of these studies came from nine countries. Seventeen studies were conducted in countries currently on the WHO list of countries with high TB burden [1325, 2729, 31]. The majority of patients were male (61.2%).…”
Section: Resultsmentioning
confidence: 99%
“…The study populations of these studies came from nine countries. Seventeen studies were conducted in countries currently on the WHO list of countries with high TB burden [1325, 2729, 31]. The majority of patients were male (61.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Gunawan and colleagues have reported abnormal EEG activity in 75% of the patients, out of them 77% had epileptogenic activities; moreover, they found a strong correlation between epileptic spikes on EEG and the development of clinical seizures [30]. However, a recent study from China has concluded that the presence of epileptiform discharge on EEG was not associated with poorer outcome [75]. In TBM patients with convulsions, epilepitform discharges are less common finding relative to slow activity, especially in adult patients.…”
Section: Eeg Findingsmentioning
confidence: 99%
“…Thus these findings were comparable to various studies. [22,23] The CSF ADA had a median of 12 U/L while mean values being 14.4 ± 6.9 U/L and 9.6 ± 4.1 U/L in studies by Kaur et al, [11] and Gambhir et al, [24] Anemia Hb< 10 gm/dl was observed in 14.2% cases which was lesser than other studies. [12,2] Hyponatremia was seen in 60% of the patients which was comparable to other studies.…”
Section: Malik and Singh: Clinical Correlates Of Tubercular Meningitismentioning
confidence: 82%